Search for pair production of vector-like quarks in the bWb‾W channel from proton–proton collisions at s=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier B.V., 2018)
A search is presented for the production of vector-like quark pairs, TT or YY, with electric charge of 2/3 (T) or −4/3 (Y), in proton–proton collisions at √s = 13 TeV. The data were collected by the CMS experiment at the LHC in 2016 and correspond to an integrated luminosity of 35.8 fb−1. The T and Y quarks are assumed to decay exclusively to a W boson and a b quark. The search is based on events with a single isolated electron or muon, large missing transverse momentum, and at least four jets with large transverse momenta. In the search, a kinematic reconstruction of the final state observables is performed, which would permit a signal to be detected as a narrow mass peak (≈7% resolution). The observed number of events is consistent with the standard model prediction. Assuming strong pair production of the vector-like quarks and a 100% branching fraction to bW, a lower limit of 1295 GeV at 95% confidence level is set on the T and Y quark masses